2012
DOI: 10.1097/cad.0b013e32834bb6b4
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo antitumour effect of daunorubicin–GnRH-III derivative conjugates on colon carcinoma-bearing mice

Abstract: Targeted cancer chemotherapy is a novel approach developed for the specific delivery of anticancer drugs. Tumour targeting can be achieved by combining a chemotherapeutic agent with a targeting moiety that recognizes tumour-specific or highly expressed receptors on cancer cells. We used the gonadotropin-releasing hormone-III (GnRH-III) as a targeting moiety to which the chemotherapeutic agent daunorubicin (Dau) was attached through an oxime bond either directly or by inserting a GFLG tetrapeptide spacer. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…This compound displayed an efficient release after disulfide reduction and exerted potent in vitro toxicity, although no comparative results with an only oxime-connected conjugate were presented [104]. However, because of the high stability, combined with a moderate toxic activity, the oxime-linked conjugate [Lys 8 (DAU = Aoa)]- GnRH-III (Aoa is aminooxyacetyl) was evaluated in vivo using healthy and colon carcinoma-bearing mice [105]. The conjugate showed significant tumor growth inhibition and no toxicity in healthy mice, in contrast to an unselective effect observed for free DAU.…”
Section: Gonadotropin-releasing Hormone-derived Peptide-drug Conjugatesmentioning
confidence: 99%
“…This compound displayed an efficient release after disulfide reduction and exerted potent in vitro toxicity, although no comparative results with an only oxime-connected conjugate were presented [104]. However, because of the high stability, combined with a moderate toxic activity, the oxime-linked conjugate [Lys 8 (DAU = Aoa)]- GnRH-III (Aoa is aminooxyacetyl) was evaluated in vivo using healthy and colon carcinoma-bearing mice [105]. The conjugate showed significant tumor growth inhibition and no toxicity in healthy mice, in contrast to an unselective effect observed for free DAU.…”
Section: Gonadotropin-releasing Hormone-derived Peptide-drug Conjugatesmentioning
confidence: 99%
“…The high expression of GnRH-I-R on several malignant tumor cells compared with healthy tissues provides an opportunity for targeted therapy 5,6 . Many gonadotropin-releasing hormone (GnRH) analogues have been developed in the last few decades, which could be used as targeting moieties 7,8,9 . These peptides are able to deliver anticancer agents with high selectivity into malignant tumor cells which over-express GnRH-I-R 6 .…”
Section: Introductionmentioning
confidence: 99%
“…These peptides are able to deliver anticancer agents with high selectivity into malignant tumor cells which over-express GnRH-I-R 6 . Several GnRH conjugated anti-tumor drugs with higher selectivity and better efficiency than the corresponding unconjugated free drug have been reported 7,8,9 . Previous publications about GnRH peptides and their receptors reported that the GnRH-I-R can assume various conformations which have different selectivity for GnRH analogues 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, various anthracycline-GnRH-III derivative bioconjugates have been designed, synthesized and biochemically characterized [10][12]. One of the most promising drug delivery systems developed to date in our laboratories consists of the anticancer drug daunorubicin (Dau) attached via an oxime bond to a GnRH-III derivative in which Ser in position 4 was replaced by Lys(Ac) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its clinical benefits, the administration of free Dau is followed by toxic side effects, the most severe one being cardiotoxicity [14], [15]. Therefore, the attachment of Dau to GnRH-based targeting moieties should provide increased selectivity and decreased systemic toxicity [12]. We have recently shown that the bioconjugate GnRH-III[ 4 Lys(Ac), 8 Lys(Dau = Aoa)] (Figure 1B) exerted in vitro cytostatic/cytotoxic effect on human breast, prostate and colon cancer cells, with IC 50 values in low μM range.…”
Section: Introductionmentioning
confidence: 99%